2014
DOI: 10.1007/s12199-014-0416-4
|View full text |Cite
|
Sign up to set email alerts
|

Biomonitoring of mercury, cadmium, and lead exposure in Japanese children: a cross-sectional study

Abstract: Objectives To measure current Hg, Cd, and Pb exposure in Japanese children, and to estimate dietary intakes of foods responsible for high body burden. Methods Blood, hair, and urine samples were collected from 9 to 10-year-old 229 children in Asahikawa and measured for Hg, Cd, and Pb in these matrices. Diet history questionnaire was used to estimate intake of marine foods and other food items. Hg level was measured by cold vapor atomic absorption spectrometry. Cd and Pb levels were determined with inductively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
2
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 32 publications
0
28
2
3
Order By: Relevance
“…Our study of blood Cd levels in Indonesian young adults living in a coastal city of Padang in West Sumatera Province showed that the median blood Cd levels (0.61 μg/L) is quite low compared to a previous study in adolescents in Iran (~ 10 μg/L (mean); [17]). However, this level was higher than that of 9-10-year-old children in Japan (0.34 μg/L (geometric mean); [18]) and 20-34 year-old general population in the US (0.27 μg/L (geometric mean); [19]). The median of blood Cd in our female subjects is lower than that of 18-24-year-old Norwegian women (0.59 vs. 1.43 μg/L; [20]).…”
Section: Discussionmentioning
confidence: 63%
“…Our study of blood Cd levels in Indonesian young adults living in a coastal city of Padang in West Sumatera Province showed that the median blood Cd levels (0.61 μg/L) is quite low compared to a previous study in adolescents in Iran (~ 10 μg/L (mean); [17]). However, this level was higher than that of 9-10-year-old children in Japan (0.34 μg/L (geometric mean); [18]) and 20-34 year-old general population in the US (0.27 μg/L (geometric mean); [19]). The median of blood Cd in our female subjects is lower than that of 18-24-year-old Norwegian women (0.59 vs. 1.43 μg/L; [20]).…”
Section: Discussionmentioning
confidence: 63%
“…Therefore, preventive steps should be taken particularly for children as different age groups have different potential health risks. In addition, children with their lightweight body masses, limited knowledge on food preference, developing nervous systems, higher intestinal absorption and lower renal excretion; are the most vulnerable group to heavy metal exposure (Ilmiawati et al, 2015;Bosch et al, 2016). Therefore with long term exposure, children are more susceptible to the risk of heavy metals toxicity especially cadmium compared to adults.…”
Section: Discussionmentioning
confidence: 99%
“…Absorption rate of cadmium in human is 3-5%. Absorbed Cd retains mainly in the kidney with a biological half time of around 10-30 years (Yuan et al 2014;Ilmiawati et al 2015;Zhang et al 2016). The urinary (uCd) and whole blood (bCd) cadmium concentration are good indicators of chronic and recent exposures, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The urinary (uCd) and whole blood (bCd) cadmium concentration are good indicators of chronic and recent exposures, respectively. The half-life of cadmium in blood is estimated to be 2-3 months (Farzin et al 2008;Ilmiawati et al 2015). Cadmium is primarily toxic for the kidney and increases the risk of cancer.…”
Section: Introductionmentioning
confidence: 99%